Honorific System in Balinese Community Stratification (Conference on English Language Teaching, 2024)
The honorific system includes a variety of words used to greet other people, which often reflect social hierarchy, status, age, and the type of relationship in an interaction between speech participants. This descriptive research aims to describe the greeting system used by the Balinese people. This research uses research data in the form of dialogue between speakers and speech partners, at family social gatherings and community social gatherings held in banjar halls in Badung district and Denpasar municipality. The observation method uses data collection techniques by listening to every interaction that occurs, recording to make it easier to collect data which will later be described according to the context of the situation and recording every interaction that occurs. Pragmatic matching techniques are used to analyze the use of greeting words, making it easier to analyze according to the objectives of the research. The results of the analysis are described using ordinary words so that they are easily understood by readers. The results of the research found that honorifics not only function as greetings but also contain the meaning of greetings spoken at the beginning of the interaction. Honorifics also change over time, due to modernization factors and social changes. However, despite this, the phenomenon of honorific systems in the context of social gathering situations still reflects traditions and cultural values. A more relaxed communication style is also becoming more common, especially among the younger generation or in more informal situations. However, honorifics will be more formal if they are in the context of a social gathering situation, in interactions with people who are older or from a higher level of society. Both in traditional stratification based on birth (caste) and modern stratification (social status). Using appropriate greetings can create a warm, friendly and respectful atmosphere among participants, while still paying attention to the social and cultural norms that apply in Bali. honorifics play an important role because they are determined by traditional social and cultural hierarchies so that the honorific system of Balinese society greatly influences social interactions, the formation of cultural identity, and ongoing changes in society. It is hoped that the results of this research will provide deeper insight into the greeting system for the community.